Effective Strategies in Developing Critical Thinking Skills in Elementary School Age Children - Rina Susanti (Westscience Press, 2024)
This study aims to identify and evaluate effective strategies in developing critical thinking skills in elementary school-age children through a literature review method. Taking into account the complexity of cognitive development at this stage, this study investigates various learning strategies that are suitable for the characteristics of elementary school-age children. Through in-depth analysis of relevant literature, this study identifies that the use of stories or fairy tales, problem-based approaches, and social interaction are effective strategies in developing critical thinking skills in elementary school-age children. Stories and fairy tales can stimulate children's imagination and reflection, while the problem-based approach encourages them to identify and solve problems critically. Social interactions, such as group discussions and teamwork, also help expand children's perspectives and hone their critical thinking skills. This study provides insights into the importance of developing critical thinking skills in elementary school-age children and offers practical guidance for educators and policymakers in designing effective learning strategies.